(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2020)
تسمح لنا نظريات البنية الجزئية بتحليل ألية عمل أسواق الأسهم وتحديد الإتجاهات الواجب اتباعها والإجابة على الأسئلة التالية: حسب أي معايير نستطيع تقييم أداء بنية تداول وخصوصاً النظام الالكتروي المستمر؟ ما هي الأثار على جودة سوق مالية ناشئة على صعيد السيولة والكفاءة المعلوماتية؟ يهدف هذا البحث إلى إجراء تحليل تطبيقي لدور نظام التداول الالكتروني المستمر وأثره في سيولة سوق مالية ناشئة وكفاءة هذا السوق. يتمحور هذا البحث حول تحليل بنيوي جزئي لأليتي التداول الدوري والمستمر وكذلك محددات السيولة. ومن ثم, جرى تنفيذ دراسة حدث, مُطبّقة على سوق تونس للأوراق المالية, بغرض التحقّق من أثار التغيرات البنيوية الحاصلة من خلال إدخال النظام الجديد المستمر للتداول على أداء السوق وسيولته. أظهرت هذه الدراسة تقدير سلبي لسيولة السوق خلال الأجل القصير, ومن ثم تبع ذلك أثر إيجابي خلال الأجل المتوسط والطويل. The theories of the microstructure en able us to analyze the way an equity market is working to give us the right directions to be taken and answer the following questions: According to which criteria can we evaluate the performance of a an exchange structure, in this case, the continuous electronic system? What are its effects on the quality of a young emerging market in terms of liquidity and informational efficiency? The objective of this research is the empirical analysis of the role of the continuous electronic exchange system on an emerging market. This research is elaborated around a microstructural analysis of an equity market, which are studied in a continuous exchange system driven by orders. We continue then with an event study applied to the Tunis Stock Exchange in order to check the effects on the performance of the market of the microstructural changes carried out by introducing the new continuous system NCS. This event was associated with a short-term negative market liquidity appreciation at the announcement of the transition to the electronic system, while the impact was positive in the medium and long term.